PENERAPAN SANKSI PIDANA TERHADAP KOTA-KOTA YANG MELAKUKAN KEKERASAN DALAM RUMAH TANGGA TERHADAP SUAMI MEREKA - Susana Kifli (The Juris, 2026)
This study aims to analyze how the application of criminal sanctions determined by the court in resolving cases of domestic violence where in this case the victim is the husband. The type of research used in this study is normative. The results of this study are in the imposition of criminal sanctions against perpetrators of domestic violence against husbands based on Law No. 23 of 20024 concerning Domestic Violence (which remains in effect complementary to Law No. 1 of 2023 concerning the new Criminal Code), which is regulated in Article 5 letter a and Article 44 of Law No. 23 of 2004 concerning the Elimination of Domestic Violence, where specifically for physical violence that does not cause illness or obstacles to carrying out daily work, this crime is a complaint offense (the legal process only runs if the husband who is the victim himself reports it). Perpetrators of light physical domestic violence can be sentenced to a maximum of 4 months in prison or a maximum fine of IDR 5 million. If the violence results in serious injury or death, the penalty is much higher, namely a maximum of 5 to 15 years in prison. Furthermore, in the New Criminal Code, there are several classifications of domestic violence that can be processed as ordinary crimes, allowing law enforcement officials to process the perpetrator even without a direct complaint from the husband as the victim. Criminal sanctions remain part of the effort to provide justice to victims of domestic violence and ensure that perpetrators of domestic violence receive appropriate punishment for their actions.